Knowledge co‐production: A pathway to effective fisheries management, conservation, and governance. Issue 2 (28th October 2020) - Cooke, Steven J.; Nguyen, Vivian M.; Chapman, Jacqueline M.; Reid, Andrea J.; Landsman, Sean J.; Young, Nathan; Hinch, Scott G.; Schott, Stephan; Mandrak, Nicholas E.; Semeniuk, Christina A.D.
Abstract : Although it is assumed that the outcomes from scientific research inform management and policy, the so‐called knowledge–action gap (i.e., the disconnect between scientific knowledge and its application) is a recognition that there are many reasons why new knowledge is not always embraced by knowledge users. The concept of knowledge co‐production has gained popularity within the environmental and conservation research communities as a mechanism of bridging the gap between knowledge and action, but has yet to be fully embraced in fisheries research. Here we describe what co‐production is, outline its benefits (relative to other approaches to research) and challenges, and provide practical guidance on how to embrace and enact knowledge co‐production within fisheries research. Because co‐production is an iterative and context‐dependent process, there is no single way to do it, but there are best practices that can facilitate the generation of actionable research through respectful and inclusive partnerships. We present several brief case studies where we describe examples of where co‐production has worked in practice and the benefits it has accrued. As more members of the fisheries science and management community effectively engage in co‐production, it will be important to reflect on the processes and share lessons with others. We submit that co‐production has manifold benefits for applied science and should lead to meaningful improvements in fisheries management, conservation, and governance.